INFLUENCE OF SUBSTRATE ENERGY ON THE ADHESION COMPATIBILITY OF EPOXY ADHESIVE USING MOLECULAR SIMULATION TOOL - AHMAD NIZAM, NUR FARAH IZZATI (IRC, 2017)
The utilization of structural adhesive onto aluminium oxide (Al₂O₃), aluminium (Al) and polyvinyl chloride (PVC) can be remarkably observed in many industrial application such as aerospace, automotive, electronics and medical. Due to the prominent properties exhibited by epoxy resin, the relevancy of opting for it as adhesive agent in the aforementioned industry is believed to be highly beneficial. However, due to lack of literature references, the feasibility of implementing the idea is still ambiguous. It is the objective of this study to shed light on those aspects especially on determining the compatibility of using epoxy resin. In fact, to avoid any undesired interfacial failure during application, evaluation of the force and energy between the epoxy resin and substrate that assesses their interaction as well as strength is also highly essential. In this study, Materials Studio 6.0 is utilized to model and simulate the compatibility and adhesion strength of epoxy resin with three different substrates i.e. aluminium oxide (Al₂O₃), aluminium (Al) and polyvinyl chloride (PVC). On the other hand, due to its establishment in the industry, the type of resin base for epoxy resin are kept constant i.e. diglycidyl ether of bisphenol A (DGEBA). The motivation of selecting such materials is to analyze the suitability of using DGEBA-based-epoxy resin as adhesive agent for each of the aforementioned substrates. In the present work, the simulation of molecular dynamics (MD) and molecular mechanics (MM) was utilized along with a forcefield called condensed phase optimized molecular potential for atomistic simulation studies (COMPASS). MD and MM simulations reveal the significant influence of substrate energy and Van der Waals force in promoting the adhesion compatibility of epoxy-substrate system. The computed result from the aforementioned simulation also shows that epoxy resin is most compatible with Al₂O₃, followed by Al and lastly with PVC.